Izzivi nastajajočih pravnih instrumentov Evropske unije in Sveta Evrope za regulacijo umetne inteligence v luči človekovih pravic - Strojin, Gregor (Podjetje in delo, 2023)
The paper discusses the context of the development of binding legal instruments for the development and use of AI in the context of human rights, and some of the challenges along the way, from awareness and calls for their necessity to their final formulation and adoption. It analyses some of the reasons that led to the creation of the need for legal standards, and the specificities of the European space that enabled activities to move from non-binding to binding legal instruments, with a focus on the Council of Europe Framework Convention and the Regulation of the European Union.
Keywords: človekove pravice; demokracija; Evropska unija; konvencija; regulacija; Sodišča; Svet Evrope; umetna inteligenca; vladavina prava